Development and characterization of solid lipid dispersion as delivery system for hydrophilic antihypertensive drug atenolol - Eman Sadder El-Leithy; Mohamed Nasr; Raghda Abd el-Moneum (International Journal of Drug Delivery, 2012)
Atenolol is a hydrophilic β-blocker drug characterized by high solubility and low permeability which corresponds to BCS class III drug. The purpose of the study was to develop solid dispersion of atenolol with fatty excipients to modify the release and enhance intestinal permeability of the drug. The solid dispersions containing atenolol were prepared using lipophilic surfactants, saturated fatty acid, triglycerides and phospholipids by co-evaporation method. The obtained solid dispersions were characterized by differential scanning calorimetry, infrared spectroscopy, drug solubility, % yield, % encapsulation efficiency and in vitro drug release. The results of in vitro release studies indicated that drug release from the drug: phosphotidylcholine dispersion (1:1w/w) showed a sustained release in comparison with the pure atenolol and the other solid dispersions. The influence of phosphotidylcholine on drug intestinal permeation was further evaluated versus pure drug. The results of in vitro permeability revealed that drug-phosphotidylcholine solid dispersion significantly enhanced % permeation of atenolol in comparison with the pure drug. This could be attributed to higher lipophilicity acquired by incorporation of the drug within the solid lipid dispersion. On the basis of the result obtained, it was concluded that solid dispersion of atenolol with phosphotidylcholine is a good approach to modify the release and enhance permeability of water soluble drug. However, the influence of lipophilic solid dispersion on atenolol bioavailability needs further investigation..